2008
DOI: 10.1073/pnas.0800603105
|View full text |Cite
|
Sign up to set email alerts
|

A polycystin-1 controls postcopulatory reproductive selection in mice

Abstract: Pkdrej, a member of the polycystin-1 gene family, is expressed only in the male germ line. Male mice that are homozygous for a targeted mutation in the Pkdrej allele (Pkdrej tm/tm ) are fertile in unrestricted mating trials, but exhibit lower reproductive success when competing with wild-type males in sequential mating trials and in artificial insemination of mixed-sperm populations. Following mating, sperm from Pkdrej tm/tm mice require >2 h longer than those of wild-type males to be detected within the egg/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 55 publications
(51 reference statements)
2
57
0
Order By: Relevance
“…For example, Pkdrej KO mice have been produced previously, and their litter size was normal, consistent with the present study (36). However, detailed analyses showed that Pkdrej KO males exhibit lower reproductive success compared with WT males in sequential mating trials, suggesting that Pkdrej is important in postcopulatory sexual selection (36).…”
Section: Discussionsupporting
confidence: 78%
“…For example, Pkdrej KO mice have been produced previously, and their litter size was normal, consistent with the present study (36). However, detailed analyses showed that Pkdrej KO males exhibit lower reproductive success compared with WT males in sequential mating trials, suggesting that Pkdrej is important in postcopulatory sexual selection (36).…”
Section: Discussionsupporting
confidence: 78%
“…Under physiological condition, before reaching the eggs, sperm must successfully migrate through the uterine-oviduct junction, where most of the sperm were blocked out and stayed in the uterine cavity. By checking the number of sperm that arrived in the egg/cumulus complex after time-defined copulation [28], we found a significant decrease in sperm/egg ratio in the Aqp3-null male ( Figure 4D and 4E), supporting the idea that the impaired in vivo fertilization in the Aqp3 -/-male is due to reduced sperm number that migrated to oviduct. Moreover, in vitro sperm transwell migration assay demonstrated that the Aqp3-null sperm showed decreased ability in passing through the mesh pores of membrane filter that mimicked the barrier of uterine-oviduct junction ( Figure 4F-4H and Supplementary information, Figure S4), which further justified our hypothesis.…”
Section: Aqp3 -/-Sperm Showed Compromised In Vivo Fertilization Due Tsupporting
confidence: 61%
“…This is likely due to the competitive nature of house mice, which vigorously compete with one another over resources. Differences in physiological performance that are too cryptic, diffuse, or subtle to cause gross defects may nonetheless lower fitness in a competitive environment and this concept has driven the use of fitness assays in Drosophila, RNA virus, and yeast communities (e.g., Shabalina et al 1997;Thatcher et al 1998;Lauring et al 2012); unfortunately, similar approaches have not been adopted by those working with vertebrate model systems (with the notable exception of genes involved in sperm function or competition, e.g., Sutton et al 2008). In addition to the Hoxb1 A1 phenotypes herein, OPAs have revealed adversities associated with three other genetic treatments, including cousin-and sibling-level inbreeding and bearing the selfish genetic element known as the t complex, which had escaped detection for decades (Meagher et al 2000;Carroll et al 2004;Ilmonen et al 2008).…”
Section: Discussionmentioning
confidence: 99%